Determinants of Financial Reporting Fraud in the Perspective of Fraud Hexagon - Annisa Rachmawati; Surya Raharja (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to detect fraud in financial statements using Fraud Hexagon analysis which includes stimulus proxied by financial stability and external pressure, opportunity proxied by effective monitoring and quality of external, rationalization proxied by change in auditors, capability proxied by change in directors, arrogance proxied by the size of CEO photos, and collusion proxied by cooperation between companies and govermemnt. This study uses the Beneish M-Score measurement to detect fraudulent financial statements. The sampling method is purposive sampling consisting of 51 companies that meet the criteria of 80 infrastructure, utility and transportation companies listed on the IDX for 2017-2022. The hypothesis in this study was tested using logistic regression analysis. The results of the study show that the variables of supervisory effectiveness, changes in directors, and cooperation between companies and the government have an influence on fraudulent financial statements. Meanwhile, the variables of financial stability, external pressure, quality of external auditors, changes in auditors, and CEO photo size have no effect on fraudulent financial statements.